1994
DOI: 10.1116/1.578987
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed ion beam surface analysis as a means of in situ real-time analysis of thin films during growth

Abstract: Low-energy (5–15 keV) pulsed ion beam surface analysis comprises several different surface spectroscopies which possess the ability to provide a remarkably wide range of information directly relevant to the growth of single and multicomponent semiconductor, metal and metal-oxide thin films and layered structures. Ion beam methods have not however, been widely used as anin situ monitor of thin film growth because existing commercial instrumentation causes excessive film damage, physically conflicts with the dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Typically connected to the PLD chamber, RHEED systems are often equipped with a differentiated vacuum pumping unit for in situ observations during thin-film deposition under a gaseous ambience [10]. Several other in situ characterization techniques, including low-energy electron diffraction, X-ray photoelectron spectroscopy, Auger electron spectroscopy, coaxial impact collision ion scattering spectroscopy, scanning probe microscope, and optical measurements, such as spectroscopic ellipsometry, have also been implemented in PLD systems [13][14][15][16][17]. Laser molecular beam epitaxy (MBE) (Figure 8.2) [11,12], which couples in situ RHEED observation with PLD for epitaxial growth, has proved to enable real-time growth control at an atomic-layer scale.…”
Section: Monitoring and Diagnostic Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically connected to the PLD chamber, RHEED systems are often equipped with a differentiated vacuum pumping unit for in situ observations during thin-film deposition under a gaseous ambience [10]. Several other in situ characterization techniques, including low-energy electron diffraction, X-ray photoelectron spectroscopy, Auger electron spectroscopy, coaxial impact collision ion scattering spectroscopy, scanning probe microscope, and optical measurements, such as spectroscopic ellipsometry, have also been implemented in PLD systems [13][14][15][16][17]. Laser molecular beam epitaxy (MBE) (Figure 8.2) [11,12], which couples in situ RHEED observation with PLD for epitaxial growth, has proved to enable real-time growth control at an atomic-layer scale.…”
Section: Monitoring and Diagnostic Toolsmentioning
confidence: 99%
“…The crystal orientation of the films depended on the background and nitrogen partial pressures as well as growth temperature. TEM observations also revealed that in-plane AlN jj [11][12][13][14][15][16][17][18][19][20] sapphire and [11][12][13][14][15][16][17][18][19][20] AlN jj [11][12][13][14][15][16][17][18][19][20] 6H-SiC were epitaxial relationships between AlN and substrate materials, respectively. Figure 8.17 shows X-ray diffraction scans of AlN films grown on sapphire (0001) and 6H-SiC (0001).…”
Section: Aluminium Nitridementioning
confidence: 99%
See 1 more Smart Citation
“…However, the shape of TOF-LEIS spectra is far more complicated than in 'electrostatic' LEIS since a large amount of multiply scattered particles is detected even for scattering angle h larger than 90°. The group of Krauss [1,2] was the first one to relate the shapes of peaks in TOF-LEIS spectra to the sample morphology when studying Pb, Zr and Ru growth on MgO and RuO 2 substrates. For layers with thicknesses below 1 ML they claim that the Gaussian shape of the LEIS peak indicates 2D growth of the film.…”
Section: Introductionmentioning
confidence: 99%
“…)03 (PZT) [29,31], Sr13iATaz09(SET) [29,32], B~5Sro,sTi03 @ST) [29], and YBazCu3@.X(YBCO) [4].~n a DRS study of S13Tdeposition onto Pt, it was demonstrated that although Pt and Bi differ in mass by 14 amu, the resolution of DRS was not sufficient to separate these two species [32]. More recently, MSRI was used to study SBT deposition onto Pt and it was shown that the resolution of MSRI was sufilcient to separate Bi (in the deposited film) from Pt (the underlying substrate) [29].…”
Section: Red-time In Situ Tof-lsars Anaivsis Of Thin Film Depositionmentioning
confidence: 99%